Confirmation of etiology in fetal hydrops by sonographic evaluation of fluid allocation patterns. (December 2015) - Hartge, David R.; Weichert, Jan; Gembicki, Michael; Krapp, Martin
Abstract: Objective: To evaluate patterns of fluid allocations in different etiologies of hydrops fetalis. Study design: This report is a retrospective cohort study on 20, 395 fetal sonographic evaluations in a single tertiary center from 2000 to 2014. Special emphasis was placed on the exact description of the distinct fluid allocation sites in each fetus. Postmortem/postnatal records were evaluated additionally. Mean follow up of the surviving neonates was 34 days (10–60 days). Results: There seem to be distinctive patterns of fluid allocation in some etiologies leading to fetal hydrops including aneuploidies and Parvovirus B19 related infections. Conclusion: Due to the allocation patterns of fluid filled sites in fetuses with hydrops fetalis the spectrum of possible etiologies may be narrowed already during initial ultrasound scan. It can contribute substantially to diagnostic accuracy as well as to parental counseling. This knowledge may also help to omit delay in diagnostic routines.